Considerable Effects of Caffeinated Coffee on Mouse Liver Function - Mostafa Rezaei Tavirani; Babak Arjmand; Mahmood Khodadoost*; Zahra Razzaghi (Iranian Society of Pharmacognosy, 2023)
Background and objectives: Coffee is a favorable drink in the world with advantages that are documented during different investigations. In the present study, the effect of caffeine which is one of the important compounds of coffee has been evaluated on function of mice liver via network analysis and gene ontology enrichment. Methods: Results of GSE53131 from Gene Expression Omnibus (GEO) were analyzed and the differentially expressed genes (DEGs) were assessed via protein-protein interaction (PPI) network analysis and gene ontology. Cytoscape software and STRING database were used to analyze the data. Results: Effect of caffeine on mice liver was appeared in the gene expression profiles of the mice liver which were fed with caffeinated and decaffeinated coffee. Acat2, Acly, Acss2, Akr1d1, Ehhadh, Elovl2, Fasn, Fdps, Gsta3, Hmgcr, Ldlr, Lss, Mmab, Mvd, Mvk, Nsdhl, Prodh, Rdh11, and Thrsp that are related mostly to lipid metabolism and cholesterol biosynthesis were pointed out as the discriminator genes in response to caffeine  effect on liver function. Conclusion: In conclusion, assessment of mice liver gene expression profiles revealed that lipid metabolism of the mice liver was affected considerably by consumption of caffeinated coffee versus liver of mice that were fed with decaffeinated coffee. Using caffeine as a preventing factor for hepatic disorders is recommended base on the findings of present study.